Self-Regulated Learning Strategy in the Learning Instructions of Interpretive Reading Courses - Ratih Laily Nurjanah; Muhammad Zaki Pahrul Hadi; Janou Willems (Journal of Languages and Language Teaching, 2024)
The integration of the SRL strategy into instructional practices is motivated by the desire to nurture students' autonomy in learning, a trait that is increasingly emphasized in contemporary educational discourse. This study investigates the integration of the Self-Regulated Learning (SRL) strategy into the instructional framework of an Interpretive Reading course. Given the emphasis on fostering students' learning independence inherent in the SRL strategy, it becomes crucial to ensure that instructional practices align with this objective, particularly within the context of a course designed for first-semester university students. The study adopts a case study approach within an Interpretive Reading class at a private university in Indonesia. Here, the focus is on evaluating the instructional strategies vis-à-vis the criteria delineated in each phase of the SRL strategy: Forethought and Planning, Monitoring of Performance, and Reflection on Performance. The findings reveal that the instructional interventions implemented by the lecturer predominantly meet the criteria established for each phase of the SRL strategy. These instructions serve as scaffolding mechanisms, guiding students towards developing their autonomy in learning processes. Furthermore, the study underscores the effectiveness of these instructions in enhancing students' interpretive reading skills. Consequently, the outcomes of this study hold implications for the integration of digital texts within the instructional context, suggesting their potential to further support and enhance student learning experiences in Interpretive Reading classrooms.